Extending the UoA Nuclear Physics Laboratory capabilities with low-γ and α spectrometers - Vasileiou, Polytimos; Mertzimekis, Theo J. (HNPS Advances in Nuclear Physics, 2019)
In this project the steps taken toward the characterization, calibration and testing of two spectroscopy stations are presented. The first one is suitable for alpha spectroscopy, consisting of a large-window silicon surface  barrier detector (SSB), a goniometric arm and a movable multiple source-holder inside a dark vacuum chamber. The second station contains two small-size, thin-window NaI(Tl) scintillators, and it is suitable for low-γ ray spectroscopy.